Experimental Study on the Effect of Strengthening Inadequate Seismically Designed Column using Pre-tensioned Steel Straps Confinement. Issue 1 (May 2020) - Tan, Jia-Yang; Ma, Chau-Khun; Chin, Chee-Loong; Zawawi Awang, Abdullah; Omar, Wahid
Abstract: Earthquake happens around the world almost every day. These phenomena have alarmed structural engineers to consider seismic actions in structural design. Research and development of strengthening inadequate seismically designed columns have become important in Malaysia. This is because most of the structures in Malaysia were not designed to resist seismic actions. Confinement has emerged as a popular and effective strengthening method under cyclic loading. In this study, two 1/6 scale reinforced concrete column specimens are tested to investigate the effect of confinement on their structural behaviour. The specimens are loaded under cyclic lateral loading with 100 mm eccentricity to explore the behaviour of RC columns under the presence of both flexural and torsional moments. The effectiveness of strengthening is evaluated based on the differences in strength, stiffness and ductility. It is shown that the strengthened specimen performed better in term of strength and ductility. However, the strengthened specimen exhibited some reduction in stiffness.